2020
DOI: 10.3390/s20195553
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Gait Parameter Prediction for OA and TKA Patients Wearing IMU Sensors

Abstract: Quantitative assessments of patient movement quality in osteoarthritis (OA), specifically spatiotemporal gait parameters (STGPs), can provide in-depth insight into gait patterns, activity types, and changes in mobility after total knee arthroplasty (TKA). A study was conducted to benchmark the ability of multiple deep neural network (DNN) architectures to predict 12 STGPs from inertial measurement unit (IMU) data and to identify an optimal sensor combination, which has yet to be studied for OA and TKA subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…With our search strategy, we did not find any paper on machine-learning algorithms for extracting gait features. However, we found a recent study [116] outside our search criteria, which implemented a deep learning approach to estimate the spatiotemporal gait features. The dataset for deep learning and the ground truth were collected from seven IMUs and motion capture combined with force plate systems, respectively, with multiple 5 m walk protocols at various speeds.…”
Section: Discussionmentioning
confidence: 99%
“…With our search strategy, we did not find any paper on machine-learning algorithms for extracting gait features. However, we found a recent study [116] outside our search criteria, which implemented a deep learning approach to estimate the spatiotemporal gait features. The dataset for deep learning and the ground truth were collected from seven IMUs and motion capture combined with force plate systems, respectively, with multiple 5 m walk protocols at various speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the appropriate neural network architecture is an important step in attaining the requisite accuracy for model predictions. In previous work, we systematically evaluated multiple neural network configurations for predicting spatiotemporal gait characteristics on this same dataset and found that convolutional neural networks yielded the highest accuracy predictions [ 28 ]. Mundt et al also compared LSTM and feedforward neural networks (FFNN) performance on time-normalized gait cycle input data and achieved better performance using the FFNN.…”
Section: Discussionmentioning
confidence: 99%
“…All the subjects who participated in this study had either end-stage osteoarthritis in the hip or knee or had recently recovered from a total joint arthroplasty. This patient population has been shown to exhibit gait adaptations, including a slower pace, shorter step length, reduced knee flexion, and increased levels of variability that may affect the generalization of the model to healthy individuals [ 28 , 48 , 49 , 50 ]. Gait measurements were taken in the laboratory environment, which may affect the subjects’ normal gait patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] Recently, an increasing number of studies reported that AI can be used in the TKA procedure. [18][19][20] For example, Karnuta et al 18 used AI to identify arthroplasty implants from radiographs of the knee. Lind et al 21 also utilised AI to identify and classify fractures of the knee.…”
mentioning
confidence: 99%